Stability of flavonoids in the presence of riboflavin-photogenerated reactive oxygen species: A kinetic and mechanistic study on quercetin, morin and rutin - Montaña, Maria Paulina (2010)
Kinetic and mechanistic aspects on the stability of the flavones (FL) quercetin (Que), morin (Mor) and rutin (Rut), in methanolic solution and in the presence of reactive oxygen species (ROS) generated by visible light-promoted riboflavin (Rf, vitamin B2) photoirradiation were studied. The system was chosen as a model for the evaluation of the in vivo protective effect of biological targets by the flavones. The overall picture includes the vitamin as an endogenous natural photosensitizer. A systematic study on the effect of ROS on FL photostability shows that under work conditions Que is oxidized by singlet molecular oxygen (O2(1Δg)), superoxide radical anion (O2̇-) and hydrogen peroxide; Mor is degraded by O2(1Δg) and O 2̇- whereas Rut only reacts with O2( 1Δg). Que and Rut, with an extremely poor overall rate constant, are mainly physical quenchers of O2( 1Δg). Mor, with O2(1Δ g)-interception ability slightly lower than the recognized synthetic antioxidant trolox (Tx), behaves as a typical sacrificial scavenger provided that ca 80% of the collisions with O2(1Δ g) cause its own degradation, whereas this parameter reaches around 50% in the case of Tx.